Formative evaluation of analytic hierarchy process as a risk prioritisation tool for risk management - Rabihah Md. Sum, (Pusat Pengajian Sains Matematik, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The aim of this study is to discover strengths and limitations of Analytic Hierarchy Process (AHP) as a risk prioritisation tool for risk management. The study developed a risk management problem and used AHP to organise and structure risks and sub-risks of the problem. It used formative evaluation method with open-ended questionnaires to obtain feedbacks from risk managers on AHP. The study documented the following strengths of AHP: it is easy to use and understand, improves understanding of a problem and improve risk assessment. AHP improves risk assessment in the following ways: it provides a systematic risk assessment process, a clear and transparent risk assessment, facilitates debate and discussion of the risk ranking, and assists risk managers to make explicit trade-off between the risks and sub-risks. AHP is useful for problems with intangible elements, scarce data or requiring subjective judgements. AHP limitations are: too many pairwise comparisons decreasing risk managers concentration and the repetitiveness of the pairwise comparisons resulting in decision fatigue. The consequence, risk managers did not answer all questions or just answer the questions randomly.